Using Hypnoteaching Strategy to Improve Students’ Writing Ability - Zuhri Dj, Muhammad; Sukarnianti, Sukarnianti (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
This research discusses about using hypnoteaching strategy to improve students’ writing ability. The objective of this research is to find out hypnoteaching strategy in improving students’ writing ability. The method used in this research was pre-experimental method by using one groups’ pretest-posttest design. The group was given pretest and posttest. Pretest was given to measure the students’ basic writing ability. After giving the pretest, taught to the students to apply hypnoteaching strategy. And the last, giving posttest, posttest was given to measure the treatments’ effect. The improvement of students’ writing ability is marked by the result of the posttest. In pretest, no one students is classified in good. After giving treatment at the experimental group, the result is 11 students get very good classification, 19 students get good classification, and only 1 student get fairly good classification. The application of hypnoteaching strategy is really helpful to improve the students’ writing ability because there was a significant writing achievement of the students after the treatment was conducted. The result of the students’ mean score and standard deviation after treatment of posttest was proved by the result of data analysis after being compare to the t-table (2.042) with t-test (80.79).